2009
DOI: 10.1007/s10875-009-9277-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 1,25 Dihydroxy Vitamin D3 Level and Expression of Vitamin D Receptor and Cathelicidin in Pulmonary Tuberculosis

Abstract: The present study suggests that PTB patients may have increased 1,25(OH)(2) D(3) levels, and this might lead to downregulation of VDR expression. Decreased VDR levels could result in defective VDR signaling. Moreover, addition of 1,25(OH)(2) D(3) might lead to increased expression of cathelicidin which could enhance the immunity against tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 28 publications
2
68
0
Order By: Relevance
“…TB patient significantly had lower VDR protein than the healthy control. The decreasing of VDR protein in TB patient might be due to VDR expression down-regulation as a result from increasing of 1,25(OH)2D3 synthesis [15,34]. The decrease might lead to defective VDR signalling due to the unavailibity of receptors for 1,25(OH)2D3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TB patient significantly had lower VDR protein than the healthy control. The decreasing of VDR protein in TB patient might be due to VDR expression down-regulation as a result from increasing of 1,25(OH)2D3 synthesis [15,34]. The decrease might lead to defective VDR signalling due to the unavailibity of receptors for 1,25(OH)2D3.…”
Section: Resultsmentioning
confidence: 99%
“…In a study in patients with pulmonary tuberculosis was reported that an increase in the level of 1,25-(OH)2D3, but the VDR protein levels decreased. Increased 1,25-(OH)2D3 may be possible to trigger the down regulation of VDR and will result low VDR signaling [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, we consider VDR, schlafen 4 (SLFN4) and XDH as particularly interesting targets for future investigations. Although a strong role for VDR signalling in human TB has already been established [68], associations of XDH and SLFN4 with TB have not been described yet. Experimental M.tb infection of KO mice deficient in these genes would be a logical first step toward their functional elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…Cathelicidin is an antimicrobial peptide expressed in response to TLR2 stimuli and vitamin D treatment in a process also involving Gp91(phox)/NADPH oxidase (NOX2, Table 1 (IV)) [67]. Among vitamin D receptor (VDR)-regulated genes, cathelicidin plays a critical role during TB [68]. Induction of the murine homolog (CAMP) was only modest in our study and no differential induction in response to M.tb of different virulence was observed, suggesting that other genes under the control of VDR could influence the host response.…”
Section: Antimycobacterial Mechanisms and Lysosomal Functionsmentioning
confidence: 99%
“…Mycobacterium tuberculosis infection leads to increased 1 ␣-hydroxylase expression and VDR upregulation in monocyte/macrophages in response to activation by TLRs (12). Furthermore, macrophages can also synthesize antimicrobial peptides such as cathelicidin, an effect that is facilitated in the presence of 25(OH)D (13). In fact, it is now being recognized that autocrine production of 1,25(OH) 2 D might also be an important negative feedback mechanism to deactivate innate and inflammatory responses of activated macrophages (14).…”
Section: Immunomodulating Effectsmentioning
confidence: 99%